The presence of Porter's sectoral clustering in Irish manufacturing - O'Donnellan, Niall (Economic & Social Studies, 1994)
Industrial clustering is seen by Porter (1990) as a dynamic process of national sectoral linkages and regional proximity that can systematically interact and reinforce each other, and which is central to international competitiveness. This article examines the extent to which Porter-type industrial clustering is currently present in Irish manufacturing, and its association, if any, with industrial performance. It also comments on the implications for industrial policy. National linkages between manufacturing sectors are not substantial; and spatial concentrations in two urban centres is more an effect of general urban economies than of sectoral linkages. Little association has been found between the clustering that is currently present in Ireland and various aspects of industrial performance.
Keywords: Industrial clusters; Manufacturing sector; Ireland; Clusters